Design of an Integrated, Six-Phase, Interleaved, Synchronous DC/DC Boost Converter on a Fuel-Cell-Powered Sport Catamaran - Michael Rimondi; Riccardo Mandrioli; Vincenzo Cirimele; Lohith Kumar Pittala; Mattia Ricco; Gabriele Grandi (Designs, 2022)
This paper describes the preliminary analysis, design and implementation phases of a DC/DC boost converter dedicated to the Futura catamaran propulsion chain developed by the UniBoAT team at the University of Bologna. The main goal of the project was the reduction of the converter’s weight by eliminating the use of heat sinks and by reducing the component size, especially inductors and capacitors. The obtained converter is directly integrated into the structure containing the fuel-cell stack. The realized converter was based on an interleaved architecture with six phases controlled through the average current mode control. The design was validated through simulations carried out using the LT-Spice software, whereas experimental validations were performed by means of both bench tests and on-field tests. Detailed thermal and efficiency analyses were provided with the bench tests under the two synchronous and non-synchronous operating modes and with the adoption of the phase-shedding technique. Prototype implementation and performance in real operating conditions are discussed in relation to on-field tests. The designed converter can be used in other applications requiring a voltage-controlled boost converter.